On Notation for Utility Theory - Wilson, Edwin B. (Quarterly Journal of Economics, 1944)
Journal Article On Notation for Utility Theory Get access Edwin B. Wilson Edwin B. Wilson Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 58, Issue 4, August 1944, Pages 647–650, https://doi.org/10.2307/1884749 Published: 01 August 1944